If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5p + 4) = 0 Reorder the terms: 5(4 + 5p) = 0 (4 * 5 + 5p * 5) = 0 (20 + 25p) = 0 Solving 20 + 25p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 25p = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 25p = 0 + -20 25p = 0 + -20 Combine like terms: 0 + -20 = -20 25p = -20 Divide each side by '25'. p = -0.8 Simplifying p = -0.8
| 12(x-7)=-3(x+2) | | 5x^4-7x^2-24=0 | | x^2-28x-2013=0 | | 3y+2*y-1= | | 4x=16-2x | | 3x-2=7x+17 | | -16t^2+48t-640=0 | | (x+4)(x-6)=7x | | 36-9a^2=0 | | -16p-5(3-4p)=2(p-4)-11 | | 4y^2-24y+20= | | 4y^2-12y-40= | | 3(-3y-3)=-9y+23 | | 11+8x=23 | | 3[4-(-2x-5)]=48x+132 | | 16t^2-140t=68 | | 10+x+14=30+5 | | 16t^2-12ft-182=0 | | 7b= | | -8x-3=4x+9 | | a+4b= | | 2x-8+7= | | 6a+9b= | | 7.3x-3.1=11.5 | | 5t^2-15+2=10 | | 8a+3b= | | X^2+2x=60 | | 7x+5(x+2)+4= | | 3p+5=30p | | 4(logx-1)=18 | | 16x^4+16x^2+3=0 | | 12a+15b= |